Design of a microfluidic strategy for trapping and screening single cells. Issue 1 (January 2016) - Occhetta, Paola; Licini, Mara; Redaelli, Alberto; Rasponi, Marco
Highlights: A microfluidic platform was designed for single cells trapping. Trapping mechanism is based on the automatic variation of hydraulic resistance. Presenting platform allowed a single cell trapping efficiency of around 40%. A chaotic mixing element was integrated to deliver patterns of particles to cells. Abstract: Traditionally, in vitro investigations on biology and physiology of cells rely on averaging the responses eliciting from heterogeneous cell populations, thus being unsuitable for assessing individual cell behaviors in response to external stimulations. In the last years, great interest has thus been focused on single cell analysis and screening, which represents a promising tool aiming at pursuing the direct and deterministic control over cause-effect relationships guiding cell behavior. In this regard, a high-throughput microfluidic platform for trapping and culturing adherent single cells was presented. A single cell trapping mechanism was implemented based on dynamic variation of fluidic resistances. A round-shaped culture chamber (Φ = 250 µm, h = 25 µm) was conceived presenting two connections with a main fluidic path: (i) an upper wide opening, and (ii) a bottom trapping junction which modulates the hydraulic resistance. Starting from eight different layouts, the chamber geometry was computationally optimized for maximizing the single cell trapping efficacy and then integrated in a polydimethylsiloxane (PDMS) microfluidic device. The final platform consists in (i) 288 chambers for trapping single cells organized in six culture units, independently addressable through the lines of (ii) a chaotic-mixer based serial dilution generator (SDG), designed for creating spatio-temporally controlled patterns of both soluble factors and non-diffusive particles. The device was experimentally validated by trapping polystyrene microspheres, featuring diameters comparable to cell size (Φ = 10 µm).